Tatalaksana Anestesi pada Pediatrik dengan Obesitas - Widyastuti, Yunita; Pratomo, Bhirowo Yudo; Taneo, Desy Chery Marlyn (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Anesthetic management of obese pediatric patients is challenging. With increasing prevalence, more childwith severely obese and comorbidities present for surgery everyday. Definition of obesity is based on bodymass index percentiles spesific to age and sex. The precursors of adult obesity-related comorbidities are often seen in obese children. Respiratory and cardiovascular comorbidities increase perioperative risk in the severely obese child. Optimal and safe anesthetic management of an obese child requires thoughtful pre prosedure assessment and meticulous perioperative management tailored to associated comorbidities, with hieghtened wareness of potential perioperative complications. There are remains a need for improved guidelines for risk stratification, drug dosing and postoperative disposition in this patient population.